2019
DOI: 10.15171/ijpni.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Development of hair care formulations containing Spirulina platensis and Ascophyllum nodosum extracts

Abstract: Introduction Hair appearance and hair care are related with self-steam and quality of life. The way hair looks it is important for women and men and can impact in self-image. 1,2 At the same time, oiliness is a condition that also affects negatively the image and self-esteem. Caused by the excessive oil production in enlarged sebaceous glands, oiliness gives skin and hair scalp a greasy appearance. 3 This way, as oiliness is a constant concern, the search for active substances that helps in oiliness control it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Among owners who administered Spirulina continuously for the 6-week trial, those who scored the coat of their pet as optimal and shiny increased more than twice between the beginning and the end of the trial. This finding is in accordance with observations of the reactions of humans to the properties of Spirulina, which made their hair shinier and easily detangled [ 59 ], increased skin health, and visibly improved hair quality [ 61 ]. The number of owners that judged the condition of the coat as optimal and shiny also increased from 50% at the end of T1 to almost 80% at T3: a result that may be correlated to the increased amounts of Spirulina provided during T2 and T3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among owners who administered Spirulina continuously for the 6-week trial, those who scored the coat of their pet as optimal and shiny increased more than twice between the beginning and the end of the trial. This finding is in accordance with observations of the reactions of humans to the properties of Spirulina, which made their hair shinier and easily detangled [ 59 ], increased skin health, and visibly improved hair quality [ 61 ]. The number of owners that judged the condition of the coat as optimal and shiny also increased from 50% at the end of T1 to almost 80% at T3: a result that may be correlated to the increased amounts of Spirulina provided during T2 and T3.…”
Section: Discussionsupporting
confidence: 91%
“…Spirulina has been amply reported in the literature to offer a valid support to the health of human skin and can thus be applied in the field of cosmetics [ 58 ]. In particular, A. Platensis has been shown to provide considerable benefits for the fibers composing the hair, making them brighter and easier to comb [ 59 ]. The benefits that Spirulina brings to the health of skin appendages probably derive from its rich nutritional profile because it has been shown that foods rich in antioxidants and omega-6 fatty acids can promote the protection of hair from oxidative stress derived from exposure to UV rays and environmental pollutants, improving shine and counteracting fall [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 The mea- formula to obtain a gloss value that is almost unaffected by the hair color. 8 These results are closer to the physical gloss definition and can more accurately express the improvement in hair cuticles. Therefore, this study used a glossymeter as an instrument to measure the glossiness of hair bundles.…”
Section: Hair Gloss By Glossymeter Gl200supporting
confidence: 57%
“…The scattered/diffuse reflected light was measured at 0°. Diffuse scattering correction can deduct the diffuse light entering the gloss channel through a special formula to obtain a gloss value that is almost unaffected by the hair color 8 . These results are closer to the physical gloss definition and can more accurately express the improvement in hair cuticles.…”
Section: Methodsmentioning
confidence: 71%